Gender Equality and Women's Empowerment: Interdisciplinary Perspectives - Jayanti Srivastava (International Journal of Women's Health Nursing And Practices, 2025)
Despite the world's progress toward gender parity in education, more girls than boys are still out of school. Despite gender equality being a fundamental human right, women and men continue to experience unequal access to opportunities and decision-making power globally. Women often face fewer opportunities for economic participation compared to men, limited access to both basic and higher education, greater health risks, and underrepresentation in politics. When women and girls are empowered, they enhance the health and productivity of their families, communities, and nations, creating a positive ripple effect for society as a whole. Gender equality means that all individuals, regardless of gender, have equal power and access to opportunities for economic independence, education, and personal development. Empowering women is a crucial step toward achieving gender equality. It involves fostering a woman's sense of self-worth, her ability to make decisions, her access to resources and opportunities, as well as her control over her own life, both at home and in the broader community, and her capacity to create positive change.
Keywords: Empowering women; Gender Parity; Human rights; gender equality; women